Peran Iklim Madrasah dan Kebersyukuran terhadap Kesejahteraan Psikologis Guru Honorer SD/MI (The Influence of Madrasah Climate and Gratitude on the Psychological Well Being of Honorary Teachers in Islamic Primary Schools (SD/MI) - Mashfiya, Wardah; Robi’ah Adawiyah, Siti; Kurniasari, Novyana; Sailin Nihlah, Silviyana; Ghufron, M. Nur (Happiness: Journal of Psychology and Islamic Science, 2025)
This study aims to analyze the influence of madrasah climate and gratitude on the psychological well-being of honorary teachers at Islamic elementary schools (Madrasah Ibtidaiyah) in Kudus Regency. The research is based on the concerning reality of honorary teachers' welfare, who often face low wages and uncertain career paths. These challenges highlight the need for psychological factors that support teachers’ motivation and mental health. The study employed a quantitative correlational approach involving 50 honorary teachers as participants. Data were collected using three Likert-scale instruments: psychological well-being, madrasah climate, and gratitude-each of which demonstrated high reliability with Cronbach’s Alpha values above 0.70. Data was analyzed using multiple linear regression. The findings show that both madrasah climate and gratitude have a significant and positive influence on teachers' psychological well-being. A conducive school environment and an internal attitude of gratitude contribute to a healthier and more productive psychological state among honorary teachers. These findings emphasize the importance of supportive or environments and spiritual values in enhancing teachers’ psychological well-being. It is recommended that madrasah administrators foster a supportive and inclusive school climate, while teachers are encouraged to cultivate gratitude as part of their psychological resilience and professional development.